Science education reform in a transitional society: the case of Rwanda - Earnest, Jaya (Sense Publishers, 2006)
Rwanda, a tiny central African nation, is a society in transition. This landlocked country was adversely affected by major political, economic and ethnic upheaval that culminated in the 1994 genocide. This chapter provides an historical overview of the transitional nation of Rwanda, describes the context of education, reviews the science education reform process and identifies the constraints and challenges faced by teachers and students in a complex transitional society. The chapter reports the result of a study that utilised quantitative and qualitative methods to examine the ongoing science education reform process. Rwanda is today faced with three major challenges~ ensuring recovery, rehabilitation and reconciliation after the genocide of 1994, overcoming the problems associated with poverty and the massive need for sustainable development. This post-conflict transitional society has now adopted the following national goals: eradication of illiteracy and poverty, universal primary education, teacher training, national capacity building in science and technology and reinforcing the teaching of mathematics and sciences (Ministry of Education 1998a, Ministry of Finance & Economic Planning, 2002). The qualitative and quantitative findings identified factors which influence the science education reform process and make meaningful interpretations of background, culture and the current situation in Rwanda. The constraints in the implementation of educational policies that involve addressing the acute shortage of teachers, lack of resources and limited finance are described in the study.